Cognitive systems engineering in health care - Bisantz, Ann M.; Burns, Catherine M. 1968-; Fairbanks, Rollin J. III (Taylor & Francis, 2015)
Cognitive systems engineering has been widely applied in the design of safety critical systems such as nuclear power, aviation, and military command-and-control. More recently, these methods are being applied to the design of health and medical systems, in order to improve health care quality, reduce errors and adverse events, and improve efficiencies. This book provides an overview of cognitive systems engineering principles in the context of healthcare, and uses state-of-the-art examples of applications in health care which can be used and adapted by health care practitioners interested in systematic engineering approaches to systems improvement